Magnetic resonance imaging findings in patients with severe neonatal indirect hyperbilirubinemia - (:unkn) unknown (B C DECKER INC, 2001)
The aim of thus study was to document the magnetic resonance imaging (MRI) findings of cases with a history of severe neonatal indirect hyperbilirubinemia. Ten cases (eight cases with neurologic findings, two normal cases) with a history of severe neonatal indirect hyperbilirubinemia were studied. Neurologic findings and MRI results were described and correlated. Seven of eight cases with neurologic findings demonstrated symmetric and uniform increased Tl signal changes limited to globus pallidi. MRI scans of two cases without neurologic findings showed no abnormality. Severe neonatal indirect hyperbilirubinemia should be considered in the differential diagnosis of bilateral symmetric hyperintense signal changes in the globus pallidus on MRI. However, high levels of unconjugated bilirubin concentrations in the neonatal period may not always cause such lesions of globus pallidus on MRI despite the presence of neurologic findings.
Keywords: MR FINDINGS; FOLLOW-UP; KERNICTERUS; BILIRUBIN; INFANTS; ENCEPHALOPATHY; LESIONS